2007
DOI: 10.3354/meps07142
|View full text |Cite
|
Sign up to set email alerts
|

CO2-induced acidification affects hatching success in Calanus finmarchicus

Abstract: Bottle incubations were conducted to examine how exposure to seawater containing 8000 ppm carbon dioxide (CO 2 ; pH 6.95) influenced the growth and reproduction of the keystone copepod Calanus finmarchicus. The chosen concentration of CO 2 is expected to occur over 100s of cubic kilometres of seawater as a result of marine CO 2 storage/disposal, and is also representative of the predicted 'worst-case' atmospheric CO 2 scenario in the year 2300. Growth (egg production and biomass loss) in adult female copepods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 38 publications
8
99
2
Order By: Relevance
“…Reports from the North Sea suggest that increasing pCO 2 will benefit gelatinous zooplankton (Attrill et al 2007), but these conclusions are based on environmental correlation rather than experimental observations, and therefore cannot illustrate causality (Haddock 2008). Data for copepods from other parts of the world show that high pCO 2 (2000-2300 latm) did not influence survival, size, development, or egg production of Acartia steueri (Kurihara et al 2004) or of Acartia tsuensis (Kurihara and Ishimatsu 2008), but that extreme values (8000 latm) did influence development (though not growth and egg production) of Calanus finmarchicus (Mayor et al 2007). Modeling suggests that the copepod Pseudocalanus sp.…”
Section: Zooplanktonmentioning
confidence: 98%
“…Reports from the North Sea suggest that increasing pCO 2 will benefit gelatinous zooplankton (Attrill et al 2007), but these conclusions are based on environmental correlation rather than experimental observations, and therefore cannot illustrate causality (Haddock 2008). Data for copepods from other parts of the world show that high pCO 2 (2000-2300 latm) did not influence survival, size, development, or egg production of Acartia steueri (Kurihara et al 2004) or of Acartia tsuensis (Kurihara and Ishimatsu 2008), but that extreme values (8000 latm) did influence development (though not growth and egg production) of Calanus finmarchicus (Mayor et al 2007). Modeling suggests that the copepod Pseudocalanus sp.…”
Section: Zooplanktonmentioning
confidence: 98%
“…At acute worst case scenario CO 2 exposures ranging between 72 hours to 9 days there was no reduction in hatching success in the copepod Acartia tsuensis and little sensitivity to elevated CO 2 during any stage of their early development [50], but there was decreased hatching success and increased naupliar mortality of the copepods Acartia erythraea [86] and decreased hatching success of Calanus finmarchicus [95] Table S2. The shrimp Palaemon pacificus also displayed variable responses at different developmental stages, pH and length of exposure [87].…”
Section: Crustaceansmentioning
confidence: 99%
“…This implies that bubbling CO 2 has a much greater effect on egg respiration than using HCl to lower pH, and is in agreement with the results obtained here in which CO 2 had a small yet significant effect at 922 ppm. Mayor et al (2007) showed that elevated CO 2 (8000 ppm) was associated with nearly an 86% reduction in hatching success of copepods despite apparently normal growth and reproduction of adults. In our experiments, there was no impact of elevated CO 2 on hatching success; however, there was an estimated 19 d delay in reaching hatching stage.…”
Section: Embryonic Developmentmentioning
confidence: 99%